Why in vitro permeation test – and not in vivo? - Maibach, Howard (Henry Stewart Talks, 2023)
In vitro Permeation test (IVPT), History of IVPT, Uses of IVPT, Vitro versus vivo, Technical details of IVPT, Percutaneous egression